Sex Differences in Estrogen Receptor Subcellular Location and Activity in Lung Adenocarcinoma Cells - Ivanova, Margarita M. (American Thoracic Society, 2010)
The role of estrogens in the increased risk of lung adenocarcinoma in women remains uncertain. We reported that lung adenocarcinoma cell lines from female, but not male, patients with non–small cell lung cancer respond proliferatively and transcriptionally to estradiol (E(2)), despite equal protein expression of estrogen receptors (ER) α and β. To test the hypothesis that nuclear localization of ERα corresponds to genomic E(2) activity in lung adenocarcinoma cells from females, cell fractionation, immunoblot, and confocal immunohistochemical microscopy were performed. We report for the first time that E(2) increases phospho-serine-118-ERα (P-ser118-ERα) and cyclin D1 (CCND1) nuclear colocalization in H1793, but not A549 lung adenocarcinoma cells, derived from a female and male patient, respectively. ERβ was primarily in the cytoplasm and mitochondria, independent of E(2) treatment, and showed no difference between H1793 and A549 cells. E(2) induced higher transcription of endogenous ERα-regulated CCND1 in H1793 than in A549 cells. Likewise, higher rapid, non-genomic E(2)-induced extracellular signal–regulated kinase 1/2 activation was detected in H1793 compared with A549 cells, linking extracellular signal–regulated kinase activation to increased P-ser118-ERα. Furthermore, E(2) increased cyclin D1 and P-ser118-ERα nuclear localization in H1793, but not A549 cells. Together, our results indicate that nuclear localization of P-ser118-ERα provides one explanation for sex-dependent differences in E(2)-genomic responses in lung adenocarcinoma cell lines.